Difficulties associated with differential diagnosis between brain metastases and foci of necrosis resulted from stereotactic radiotherapy (case report and literature review) - А. V. Nazarenko; Т. N. Borisova; S. V. Medvedev; S. I. Tkachev; Е. А. Kobyakova; E. А. Nechipay; D. S. Romanov; N. А. Kozlov; D. V. Sashin; А. Kh. Bekyashev; D. R. Naskhletashvili; Е. А. Moskvina; et al. (Опухоли головы и шеи, 2019)
Modern advances in oncology can achieve significantly better results in terms of life expectancy in patients with metastatic brain disease. The combination of surgery, systemic therapy, whole brain irradiation and local methods of radiation therapy lead to good indicators for controlling the manifestations of the disease in the brain. Of course, intensification of treatment increases the risk of iatrogenic complications. The use of aggressive stereotactic radiotherapy regimens leads not only to high local control of irradiated metastases, but also to the risk of so-called radiation necrosis. The use of the most up-to-date diagnostic methods does not always allow one to unequivocally differentiate radiation necrosis from continued metastasis growth. The above example shows the need for a careful assessment of such situations and a multidisciplinary approach to interpreting the results of stereotactic radiotherapy.